2011
DOI: 10.2174/2210289201102010064
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic Acid as a Novel Drug Delivery Vector: Synergy of Drug Transport and Efficacy

Abstract: Supramolecular drug delivery systems (DDS) are widely used in pharmacology during last decades for designing new preparations with improved properties. Most of fundamental and applied research in this field has been devoted to the inclusion complexes with cyclodextrins (CD), which are assumed to possess protective properties and to decrease the hydrophobic behavior of the included molecules. At present a new generation of DDS has been developing. Novel DDS are focused simultaneously on several purposes, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 53 publications
(90 reference statements)
1
18
0
Order By: Relevance
“…At the same time, toxicity decreases by 1.7 times, and the amplitude of the therapeutic index increases by 17 times (Tolstikova et al, 2009). Similar action was detected for complexation of glycyrrhizin with other drugs, for example, nifedipine complexes with GA manifested antihypertensive therapeutic effect in a ten-fold reduced dose of nifedipine (Tolstikova et al, 2009;Polyakov and Leshina, 2011). The anti-inflammatory activity of GA and salbutamol was tested using tumor necrosis factor-alpha-induced NF-kappaB transcriptional activation reporter assay, I-kappaB Western blotting and interleukin-8 ELISA.…”
Section: Complex Formation With Drugssupporting
confidence: 57%
See 1 more Smart Citation
“…At the same time, toxicity decreases by 1.7 times, and the amplitude of the therapeutic index increases by 17 times (Tolstikova et al, 2009). Similar action was detected for complexation of glycyrrhizin with other drugs, for example, nifedipine complexes with GA manifested antihypertensive therapeutic effect in a ten-fold reduced dose of nifedipine (Tolstikova et al, 2009;Polyakov and Leshina, 2011). The anti-inflammatory activity of GA and salbutamol was tested using tumor necrosis factor-alpha-induced NF-kappaB transcriptional activation reporter assay, I-kappaB Western blotting and interleukin-8 ELISA.…”
Section: Complex Formation With Drugssupporting
confidence: 57%
“…Only in last decades in addition to its own therapeutic activity, a novel unusual property of the GA has been discovered. In particular, the ability of GA to form inclusion complexes with a variety of drugs was demonstrated (Baltina, 2003;Apanasenko et al, 2015;Polyakov et al, 2008;Tolstikova et al, 2009;Polyakov and Leshina, 2011;Polyakov et al, 2013). These complexes show significant advantages over other known DDS.…”
Section: Introductionmentioning
confidence: 99%
“…Third, it was reported that GA increases drug permeability not only due to increased solubility but also due to increased drug permeability through cell membranes. 20,36 Na 2 GA has similar properties to GA and can penetrate more into the cells than SN-38 suspension, therefore leading to a better bioavailability.…”
Section: Pharmacokinetics Studymentioning
confidence: 99%
“…Disodium glycyrrhizinate (Na 2 GA) is the salt of glycyrrhizic acid (GA) which can undergo hydrolysis in aqueous solutions and form a free GA. Like GAs, it has anti-inflammatory and anti-cancer properties, 20 and the resulting solution is less viscous and can help improve the solubility and permeability of hydrophobic drugs. 21 Considering the environmentfriendly and low-cost mechanochemical techniques and potential dissolution enhancement ability of Na 2 GA, an amorphous solid dispersion of SN-38 was prepared by mechanical milling, which was combined with Na 2 GA. 22 Moreover, we evaluated the physical characteristics, dissolution law, in vitro and in vivo properties, pharmacokinetics, tissue distribution, and antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction. At present more and more attention is paid to the methods of obtaining molecular complexes of different biologically active substances with plant saponins and the elaboration of novel medical preparations on their basis [1][2][3][4][5][6][7][8][9]. In particular, the complexes with aromatic amino acids were synthesized.…”
mentioning
confidence: 99%